(untitled) (Dhaka University Journal of Science, 2020)
A herbicide, 2,4-dichlorophenoxyacetic acid was attempted to incorporate in a polymeric system with a view to control/slow down its release. Jute fiber has been used as a biodegradable, eco-friendly source of cellulose which served the macromolecular backbone for polymeric matrix. Dual application of polymer supported herbicide has been attempted by choosing acrylamide as grafting monomer which on release can also act as soil-modifier (fertilizer). Jute fiber was delignified with alkali and bleached to pulping and then grafted with acrylamide to form a polymeric network. This pre-formed polymer was then subjected to esterification reaction with 2,4-dichlorophenoxyacetic acid and the product thus obtained was analyzed with Fourier transform infrared spectroscopy, with the help of attenuated total reflectance as a sampling technique followed by determining the water absorbency. From the study, it was also found that xylene was the best choice of solvent for 2,4-dichlorophenoxyacetic acid, as it can keep the product from aqueous solution, as a consequence of which, higher esterification was favored. It is proposed that the above formulation could be opted for control/slower release of 2,4- dichlorophenoxyacetic acid and can also serve the multiple functions of herbicide and fertilizer or soil nutrient. Dhaka Univ. J. Sci. 68(2): 105-110, 2020 (July)